Neonatal Fc Receptor: From Immunity to Therapeutics - Kuo, Timothy T. (Springer US, 2010)
The neonatal Fc receptor (FcRn), also known as the Brambell receptor and encoded by Fcgrt, is a MHC class I like molecule that functions to protect IgG and albumin from catabolism, mediates transport of IgG across epithelial cells, and is involved in antigen presentation by professional antigen presenting cells. Its function is evident in early life in the transport of IgG from mother to fetus and neonate for passive immunity and later in the development of adaptive immunity and other functions throughout life. The unique ability of this receptor to prolong the half-life of IgG and albumin has guided engineering of novel therapeutics. Here, we aim to summarize the basic understanding of FcRn biology, its functions in various organs, and the therapeutic design of antibody- and albumin-based therapeutics in light of their interactions with FcRn.